Pelatihan Inovasi Marketplace Bagi UMKM - Suhermin; Yesa Cahayaning Rarnadhani; Budianto; Anang Subardjo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Technological progress is something that cannot be avoided in today's life, because technological progress will run in accordance with scientific advances. The platforms that are often used in digital marketing are social media or social networks. The available social networks sometimes have different characteristics. Constraints for SMEs in Semampir Subdistrict, Surabaya City, who do not fully understand the motivation of driving products to do something good or bad or negative and positive, as well as providing a driving force that creates enthusiasm for one's work so that they want to work with all their efforts to achieve satisfaction. The next problem is the lack of knowledge about the marketplace for MSMEs. Most MSMEs do not really understand the marketplace, especially e-commerce. The method uses offline technical guidance and as a result of the training, MSMEs understand how to use technology applications and can innovate and be creative rapidly